2013
DOI: 10.3390/f4040751
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution and Volume of Dead Wood in Unmanaged Caspian Beech (Fagus orientalis) Forests from Northern Iran

Abstract: Unmanaged forests are remnants of natural ecosystems that provide a basis for close-to-nature silvicultural research and applications. These forests have high amounts of dead wood, and although this material is being increasingly studied, the diversity of dead wood in terms of different diameters, decay stages, and spatial distribution patterns is as important as its volume for understanding forest dynamics. Here, we study natural forests in northern Iran to investigate the spatial distribution, decay stages, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 43 publications
1
11
1
Order By: Relevance
“…In this study we found a mean CWD volume of 74.6 ± 18.1 m 3 ha -1 with a range of 1.2-136.1 m 3 ha -1 , similar to several other studies carried out in the Iranian beech forests (Sefidi et al 2013, Amanzadeh et al 2013, Sefidi & Marvie-Mohadjer 2010. Contrastingly, the total volume of dead timber at the Milesice Forest Reserve in the Czech Republic reached 324 m 3 ha -1 (Vrska et al 2001), that was higher than our findings.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study we found a mean CWD volume of 74.6 ± 18.1 m 3 ha -1 with a range of 1.2-136.1 m 3 ha -1 , similar to several other studies carried out in the Iranian beech forests (Sefidi et al 2013, Amanzadeh et al 2013, Sefidi & Marvie-Mohadjer 2010. Contrastingly, the total volume of dead timber at the Milesice Forest Reserve in the Czech Republic reached 324 m 3 ha -1 (Vrska et al 2001), that was higher than our findings.…”
Section: Discussionsupporting
confidence: 91%
“…The same authors found a greater CWD volume on more fertile north-facing slopes than on south-facing slopes. Moreover, in the north of Iran Alidadi et al (2015) showed dead wood decomposition rates of F. orientalis and Carpinus betulus significantly different between north facing and south facing slopes (Alidadi 2013). In this study, slope aspect was not significantly correlated with CWD volume or density, despite an accumulation of CWD in north-facing slopes was expected.…”
Section: Iforest -Biogeosciences and Forestrycontrasting
confidence: 40%
See 1 more Smart Citation
“…Oheimb et al (2007) found the same pattern in a temperate near-natural beech forest in Germany; in an 8-ha sample plot, the overall spatial distribution of dead trees exhibited a random pattern, whereas uprooted beech trees deviated from random to an aggregated pattern. In unmanaged Caspian beech forests in Iran, Amanzadeh et al (2013) observed a random spatial pattern of dead trees in two plots and detected significant spatial aggregation in only one plot, a plot governed by high density-dependent competition (selfthinning). Conversely, a significant aggregated pattern of standing and fallen dead trees was detected in Albanian virgin beech forests according to Meyer et al (2003).…”
Section: Discussionmentioning
confidence: 96%
“…Although old-growth forests may serve as a reference for managed forests, providing important information for conservation and promoting biodiversity, few studies have examined quantity and quality (dead wood types, decay classes), size class distribution and spatial patterns of dead trees in natural forests (Oheimb et al, 2007;Rahman et al, 2008;Amanzadeh et al, 2013), mainly due to the scarcity and inaccessibility of remnant virgin forests. In particular, this applies to remnant natural beech forests in Southeastern Europe.…”
Section: Introductionmentioning
confidence: 99%